Dynamics of Large Corporate Forestland Ownerships in the United States - Emma M Sass; Marla Markowski-Lindsay; Brett J Butler; Jesse Caputo; Andrew Hartsell; Emily Huff; Amanda Robillard (Journal of Forestry, 2021)
Ownership of forestland in the United States has changed in recent decades, including the proliferation of timber investment management organizations (TIMOs) and real estate investment trusts (REITs), with the potential to alter forest management and timber supply. This article quantifies forest ownership transitions among ownership categories between 2007 and 2017 and investigates how and why large corporate ownerships own and manage their forestlands. Ownership transitions were determined from refined USDA Forest Service, Forest Inventory and Analysis data; we also conducted a survey of large corporate forestland ownerships. Corporate forestland acreage increased between 2007 and 2017, while family and public forestland decreased. Large corporate landowners report multidimensional, financially focused land management, although industry, timber investment management organizations, real estate investment trusts, and other owners report some different motivations and income streams. This work provides a baseline to track future ownership transitions and the behaviors of large corporate forestland owners.